Estimasi Biaya Konstruksi Pada Perumahan Tipe 45 di Sulawesi Tengah Menggunakan Regresi Kuadratik - Rizal, A.; Fajri, M.; Yuniar, L.S. (Civil Engineering Department, Tadulako University, 2020)
his research is based on the background of the problem that cost estimation is very beneficial for the owner, contractor and consultant. Errors in estimating costs are very often done, this is due to lack of experience and information obtained by an estimator. The purpose of this study is to obtain an equation that can help an estimator in estimating costs whose results approach the actual cost and can speed up the estimation process. The data that used in this research is from RAB’s 45 type house in Central Sulawesi. The method that will be used in this research is Pearson Correlation and Quadratic Regression. Pearson correlation is used to see the correlation between the independent and dependent variables while the Quadratic Regression is used to get the equation between the independent variable and the dependent variable. Regression modeling results obtained are y=-649,15X1+0,0022X1^2+182X3-0.0005X3^2+e, with R2 = 95%. The variables that significant in this research are raw material ( X1) and concrete brick ( X3)